The Diet Of The Prophet (Peace Be Upon Him) And Its Relation To Kulliyyāt Al-Khams: An Islamic And Scientific Perspective - Mohd Hussain, Muhammad Hafis; Mustapha, Ramlan; Mohamed, Asjad; Ismail, Mohd Khairi; Kirin, Arwansyah (2024)
The dietary guidance taught by the Prophet (PBUH), as contained in his hadiths, is part of Islamic legislation. Shariah, as widely known, comprises the Qur’an, the Sunnah, qiyas (analogical reasoning), and ijma' (consensus of scholars). All these sources encompass objectives and wisdom, collectively referred to as maqāṣid al-sharīᶜah. The question that arises is how the dietary guidance taught by the Prophet (PBUH) can be linked to maqāṣid al-sharīᶜah. This study aims to examine and analyze the maqāṣid al-sharīᶜah embedded in the dietary guidance of the Prophet (PBUH), or more precisely, his diet. The research employs a qualitative approach, using a library-based method to gather data relevant to the topic. The findings reveal that the Prophet’s dietary practices encompass legislative wisdom closely related to the Kulliyyat al-Khams (the five fundamental principles of maqāṣid al-sharīᶜah): the preservation of religion, life, intellect, wealth, and lineage. The study is further supported by scientific evidence related to nutrition, which reinforces the relevance of the Prophet’s dietary guidance in the context of maqāṣid al-sharīᶜah.